Plus, Minus, Interesting (PMI) Technique: A Solution for Teaching English Writing - Miany, Resy; Puspitasari, Maydinda Ayu; Larasati, Daning; Sutiyono, Akhmad; Marcela, Eny Dwi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The research aimed to know the influence of Plus, Minus, Interesting (PMI) technique towards students’ writing ability at SMA YP UNILA Bandar Lampung. In this research the writer used experimental method or know a descriptive quantitative research. The population was 246 students in 8 classes. The sample was collected using the cluster random sampling approach. The writer used two classes as research samples: XI IPS 1 as an experimental class with 30 students and XI IPA 8 as a control class with 30 students. It consisted of 60 students. In collecting the data, the writer used writing test to measure students' writing ability. The writer used t-test formula to calculate the data analysis. According to the data analysis, the writer got the result that was accepted. It was obtained that 3.39, for was 1.68 and for 0.01was 2.42 (3.39> 1.68 < 2.42). So, was accepted. It means that there was significant influence of Plus, Minus, Interesting (PMI) Technique Towards Students’ Writing Ability at The Eleventh Grade of SMA YP UNILA Bandar Lampung in academic year 2022/2023. And the average score of students’ writing ability who was taught through Plus, Minus, Interesting (PMI) Technique was higher than conventional technique. It was 65.5 > 58. Based on the result of the research, it is clear that students’ Plus, Minus, Interesting (PMI) has good effect to students’ writing ability